2023
DOI: 10.3390/w15030456
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate and Human Activity Effects on Hypersaline Lake Ecosystem: Case Study of Saki Lake, Crimea

Abstract: In the Crimean Peninsula, there are several hypersaline lakes that have hydromineral and biological resources. However, they are under a significant anthropogenic load, which together with the climate change leads to negative consequences for the ecosystems. The aim of the work was to study the seasonal changes of physicochemical parameters of water (temperature, pH, oxygen content, salinity, redox potential Eh, optical density and transparency) and Artemia population in Saki Lake in 2022. For the daily fluctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…With careful planning and implementation of the best management practices for erosion and sediment control, the consequences of development on receiving water bodies can be minimized. A similar study suggested that sustainability management is possible for the restoration of hypersaline wetlands by assessing seasonal fluctuations of water quality parameters and their potential effects due to climate change [87].…”
Section: Management Of the Reservementioning
confidence: 97%
“…With careful planning and implementation of the best management practices for erosion and sediment control, the consequences of development on receiving water bodies can be minimized. A similar study suggested that sustainability management is possible for the restoration of hypersaline wetlands by assessing seasonal fluctuations of water quality parameters and their potential effects due to climate change [87].…”
Section: Management Of the Reservementioning
confidence: 97%
“…Therefore, the primary objectives of this study were enhancing the economic efficiency of mineral water extraction while minimizing environmental threats. With those in mind, we set out to analyze hydrogeological processes under random influences, find methods and algorithms for management, and identify laws for optimal functioning of the technological process [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It includes the following republics of the North Caucasus Federal District: Karachay-Cherkessia, Kabardino-Balkaria and the Stavropol Territory. The area of the resort is 5243 km 2 [1][2][3]. The Government of the Russian Federation has assigned this territory the status of an ecological resort region, where economic activities are regulated by a special regime of environmental management.…”
Section: Introductionmentioning
confidence: 99%